CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Yuan, Bo; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exons; Humans; INDEL Mutation; Retrospective Studies; Whole Exome Sequencing

Likely damaging de novo variants in congenital diaphragmatic hernia patients are associated with worse clinical outcomes. - Qiao, Lu; Wynn, Julia; Yu, Lan; Hernan, Rebecca; Zhou, Xueya; Duron, Vincent; Aspelund, Gudrun; Farkouh-Karoleski, Christiana; Zygumunt, Annette; Krishnan, Usha S; Nees, Shannon; Khlevner, Julie; et al. (Genet Med, 2020)
PURPOSE: Congenital diaphragmatic hernia (CDH) is associated with significant mortality and long-term morbidity in some but not all individuals. We hypothesize monogenic factors that cause CDH are likely to have pleiotropic effects and be associated with worse clinical outcomes. METHODS: We enrolled and prospectively followed 647 newborns with CDH and performed genomic sequencing on 462 trios to identify de novo variants. We grouped cases into those with and without likely damaging (LD) variants and systematically assessed CDH clinical outcomes between the genetic groups. RESULTS: Complex cases with additional congenital anomalies had higher mortality than isolated cases (P = 8 × 10). Isolated cases with LD variants had similar mortality to complex cases and much higher mortality than isolated cases without LD (P = 3 × 10). The trend was similar with pulmonary hypertension at 1 month. Cases with LD variants had an estimated 12-17 points lower scores on neurodevelopmental assessments at 2 years compared with cases without LD variants, and this difference is similar in isolated and complex cases. CONCLUSION: We found that the LD genetic variants are associated with higher mortality, worse pulmonary hypertension, and worse neurodevelopment outcomes compared with non-LD variants. Our results have important implications for prognosis, potential intervention and long-term follow up for children with CDH.
Keywords: Child; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Retrospective Studies

Molecular diagnosis in recessive pediatric neurogenetic disease can help reduce disease recurrence in families. - Issa, Mahmoud Y; Chechlacz, Zinayida; Stanley, Valentina; George, Renee D; McEvoy-Venneri, Jennifer; Belandres, Denice; Elbendary, Hasnaa M; Gaber, Khaled R; Nabil, Ahmed; Abdel-Hamid, Mohamed S; Zaki, MAH S; Gleeson, Joseph G (BMC Med Genomics, 2020)
BACKGROUND: The causes for thousands of individually rare recessive diseases have been discovered since the adoption of next generation sequencing (NGS). Following the molecular diagnosis in older children in a family, parents could use this information to opt for fetal genotyping in subsequent pregnancies, which could inform decisions about elective termination of pregnancy. The use of NGS diagnostic sequencing in families has not been demonstrated to yield benefit in subsequent pregnancies to reduce recurrence. Here we evaluated whether genetic diagnosis in older children in families supports reduction in recurrence of recessive neurogenetic disease. METHODS: Retrospective study involving families with a child with a recessive pediatric brain disease (rPBD) that underwent NGS-based molecular diagnosis. Prenatal molecular testing was offered to couples in which a molecular diagnosis was made, to help couples seeking to prevent recurrence. With this information, families made decisions about elective termination. Pregnancies that were carried to term were assessed for the health of child and mother, and compared with historic recurrence risk of recessive disease. RESULTS: Between 2010 and 2016, 1172 families presented with a child a likely rPBD, 526 families received a molecular diagnosis, 91 families returned to the clinic with 101 subsequent pregnancies, and 84 opted for fetal genotyping. Sixty tested negative for recurrence for the biallelic mutation in the fetus, and all, except for one spontaneous abortion, carried to term, and were unaffected at follow-up. Of 24 that genotyped positive for the biallelic mutation, 16 were electively terminated, and 8 were carried to term and showed features of disease similar to that of the older affected sibling(s). Among the 101 pregnancies, disease recurrence in living offspring deviated from the expected 25% to the observed 12% ([95% CI 0·04 to 0·20], p = 0·011). CONCLUSIONS: Molecular diagnosis in an older child, coupled with prenatal fetal genotyping in subsequent pregnancies and genetic counselling, allows families to make informed decisions to reduce recessive neurogenetic disease recurrence.
Keywords: Child, Preschool; Female; Genes, Recessive; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Nervous System Diseases; Pedigree; Pregnancy; Prenatal Diagnosis; Recurrence; Retrospective Studies

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

Genotype-phenotype investigation of 35 patients from 11 unrelated families with camptodactyly-arthropathy-coxa vara-pericarditis (CACP) syndrome. - Yilmaz, Saliha; Uludağ Alkaya, Dilek; Kasapcopur, Ozgur; Barut, Kenan; Akdemir, Ekin S; Celen, Cemre; Youngblood, Mark W; Yasuno, Katsuhito; Bilguvar, Kaya; Günel, Murat; Tuysuz, Beyhan (Mol Genet Genomic Med, 2018)
BACKGROUND: The camptodactyly-arthropathy-coxa vara-pericarditis syndrome (CACP) is a rare autosomal recessive condition characterized by camptodactyly, noninflammatory arthropathy, coxa vara, and pericarditis. CACP is caused by mutations in the proteoglycan 4 (PRG4) gene, which encodes a lubricating glycoprotein present in the synovial fluid and at the surface of articular cartilage. METHODS: In the present study, we compared the clinical and molecular findings of CACP syndrome in 35 patients from 11 unrelated families. In 28 patients, whole exome sequencing was used to investigate genomic variations. RESULTS: We found that camptodactyly of hands was the first symptom presented by most patients. Swelling of wrists, knees, and elbows began before 4 years of age, while the age of joint involvement was variable. Patients reported an increased pain level after the age of 10, and severe hip involvement developed after 20 years old. All patients presented developmental coxa vara and seven patients (~22%) had pleural effusion, pericarditis, and/or ascites. We identified nine novel genomic alterations, including the first case of homozygous complete deletion of exon 1 in the PRG4 gene. CONCLUSION: With this study, we contribute to the catalog of CACP causing variants. We confirm that the skeletal component of this disease worsens with age, and presents the potential mechanisms for interfamily variability, by discussing the influence of a modifier gene and escape from nonsense-mediated mRNA decay. We believe that this report will increase awareness of this familial arthropathic condition and the characteristic clinical and radiological findings will facilitate the differentiation from the common childhood rheumatic diseases such as juvenile idiopathic arthritis.
Keywords: Adolescent; Adult; Arthropathy, Neurogenic; Child; Child, Preschool; Coxa Vara; Exons; Female; Genetic Association Studies; Hand Deformities, Congenital; Humans; Male; Middle Aged; Mutation; Proteoglycans; Retrospective Studies; Sequence Deletion; Synovitis; Whole Exome Sequencing

Identification of novel candidate disease genes from de novo exonic copy number variants. - Gambin, Tomasz; Yuan, Bo; Bi, Weimin; Liu, Pengfei; Rosenfeld, Jill A; Coban-Akdemir, Zeynep; Pursley, Amber N; Nagamani, Sandesh C S; Marom, Ronit; Golla, Sailaja; Dengle, Lauren; Petrie, Heather G; et al. (Genome Med, 2017)
BACKGROUND: Exon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype-phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery. METHODS: We retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray analysis (CMA) at Baylor Genetics laboratories, including 46,755 individuals tested using exon-targeted arrays, from 2007 to 2017. Small CNVs harboring a single gene or two to five non-disease-associated genes were identified; the genes involved were evaluated for a potential disease association. RESULTS: In this clinical population, among rare CNVs involving any single gene reported in 7200 patients (11%), we identified 145 de novo autosomal CNVs (117 losses and 28 intragenic gains), 257 X-linked deletion CNVs in males, and 1049 inherited autosomal CNVs (878 losses and 171 intragenic gains); 111 known disease genes were potentially disrupted by de novo autosomal or X-linked (in males) single-gene CNVs. Ninety-one genes, either recently proposed as candidate disease genes or not yet associated with diseases, were disrupted by 147 single-gene CNVs, including 37 de novo deletions and ten de novo intragenic duplications on autosomes and 100 X-linked CNVs in males. Clinical features in individuals with de novo or X-linked CNVs encompassing at most five genes (224 bp to 1.6 Mb in size) were compared to those in individuals with larger-sized deletions (up to 5 Mb in size) in the internal CMA database or loss-of-function single nucleotide variants (SNVs) detected by clinical or research whole-exome sequencing (WES). This enabled the identification of recently published genes (BPTF, NONO, PSMD12, TANGO2, and TRIP12), novel candidate disease genes (ARGLU1 and STK3), and further confirmation of disease association for two recently proposed disease genes (MEIS2 and PTCHD1). Notably, exon-targeted CMA detected several pathogenic single-exon CNVs missed by clinical WES analyses. CONCLUSIONS: Together, these data document the efficacy of exon-targeted CMA for detection of genic and exonic CNVs, complementing and extending WES in clinical diagnostics, and the potential for discovery of novel disease genes by genome-wide assay.
Keywords: Cohort Studies; DNA Copy Number Variations; Exons; Genetic Diseases, Inborn; Genome, Human; Homeodomain Proteins; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Neurodevelopmental Disorders; Protein-Serine-Threonine Kinases; Retrospective Studies; Transcription Factors; Whole Genome Sequencing

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
Importance: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. Objective: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. Design, Setting, and Participants: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. Main Outcomes and Measures: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. Results: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. Conclusions and Relevance: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas; Whole Exome Sequencing

Assessment of estimated retinal atrophy progression in Stargardt macular dystrophy using spectral-domain optical coherence tomography. - Strauss, Rupert W; Muñoz, Beatriz; Wolfson, Yulia; Sophie, Raafay; Fletcher, Emily; Bittencourt, Millena G; Scholl, Hendrik P N (Br J Ophthalmol, 2016)
AIMS: To estimate disease progression based on analysis of macular volume measured by spectral-domain optical coherence tomography (SD-OCT) in patients affected by Stargardt macular dystrophy (STGD1) and to evaluate the influence of software errors on these measurements. METHODS: 58 eyes of 29 STGD1 patients were included. Numbers and types of algorithm errors were recorded and manually corrected. In a subgroup of 36 eyes of 18 patients with at least two examinations over time, total macular volume (TMV) and volumes of all nine Early Treatment of Diabetic Retinopathy Study (ETDRS) subfields were obtained. Random effects models were used to estimate the rate of change per year for the population, and empirical Bayes slopes were used to estimate yearly decline in TMV for individual eyes. RESULTS: 6958 single B-scans from 190 macular cube scans were analysed. 2360 (33.9%) showed algorithm errors. Mean observation period for follow-up data was 15 months (range 3-40). The median (IQR) change in TMV using the empirical Bayes estimates for the individual eyes was -0.103 (-0.145, -0.059) mm per year. The mean (±SD) TMV was 6.321±1.000 mm at baseline, and rate of decline was -0.118 mm per year (p=0.003). Yearly mean volume change was -0.004 mm in the central subfield (mean baseline=0.128 mm), -0.032 mm in the inner (mean baseline=1.484 mm) and -0.079 mm in the outer ETDRS subfields (mean baseline=5.206 mm). CONCLUSIONS: SD-OCT measurements allow monitoring the decline in retinal volume in STGD1; however, they require significant manual correction of software errors.
Keywords: Adolescent; Adult; Aged; Child; Disease Progression; Female; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Reproducibility of Results; Retrospective Studies; Tomography, Optical Coherence; Visual Acuity; Young Adult

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

A visual and curatorial approach to clinical variant prioritization and disease gene discovery in genome-wide diagnostics. - James, Regis A; Campbell, Ian M; Chen, Edward S; Boone, Philip M; Rao, Mitchell A; Bainbridge, Matthew N; Lupski, James R; Yang, Yaping; Eng, Christine M; Posey, Jennifer E; Shaw, Chad A (Genome Med, 2016)
BACKGROUND: Genome-wide data are increasingly important in the clinical evaluation of human disease. However, the large number of variants observed in individual patients challenges the efficiency and accuracy of diagnostic review. Recent work has shown that systematic integration of clinical phenotype data with genotype information can improve diagnostic workflows and prioritization of filtered rare variants. We have developed visually interactive, analytically transparent analysis software that leverages existing disease catalogs, such as the Online Mendelian Inheritance in Man database (OMIM) and the Human Phenotype Ontology (HPO), to integrate patient phenotype and variant data into ranked diagnostic alternatives. METHODS: Our tool, "OMIM Explorer" ( http://www.omimexplorer.com ), extends the biomedical application of semantic similarity methods beyond those reported in previous studies. The tool also provides a simple interface for translating free-text clinical notes into HPO terms, enabling clinical providers and geneticists to contribute phenotypes to the diagnostic process. The visual approach uses semantic similarity with multidimensional scaling to collapse high-dimensional phenotype and genotype data from an individual into a graphical format that contextualizes the patient within a low-dimensional disease map. The map proposes a differential diagnosis and algorithmically suggests potential alternatives for phenotype queries--in essence, generating a computationally assisted differential diagnosis informed by the individual's personal genome. Visual interactivity allows the user to filter and update variant rankings by interacting with intermediate results. The tool also implements an adaptive approach for disease gene discovery based on patient phenotypes. RESULTS: We retrospectively analyzed pilot cohort data from the Baylor Miraca Genetics Laboratory, demonstrating performance of the tool and workflow in the re-analysis of clinical exomes. Our tool assigned to clinically reported variants a median rank of 2, placing causal variants in the top 1 % of filtered candidates across the 47 cohort cases with reported molecular diagnoses of exome variants in OMIM Morbidmap genes. Our tool outperformed Phen-Gen, eXtasy, PhenIX, PHIVE, and hiPHIVE in the prioritization of these clinically reported variants. CONCLUSIONS: Our integrative paradigm can improve efficiency and, potentially, the quality of genomic medicine by more effectively utilizing available phenotype information, catalog data, and genomic knowledge.
Keywords: Computational Biology; Diagnosis, Differential; Disease; Genetic Variation; Genome-Wide Association Study; Humans; Phenotype; Pilot Projects; Retrospective Studies; Software

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic Americans; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

Successful diagnosis of HIBCH deficiency from exome sequencing and positive retrospective analysis of newborn screening cards in two siblings presenting with Leigh's disease. - Stiles, Ashlee R; Ferdinandusse, Sacha; Besse, Arnaud; Appadurai, Vivek; Leydiker, Karen B; Cambray-Forker, E J; Bonnen, Penelope E; Abdenur, Jose E (Mol Genet Metab, 2015)
PURPOSE: 3-Hydroxyisobutryl-CoA hydrolase (HIBCH) deficiency is a rare disorder of valine metabolism. We present a family with the oldest reported subjects with HIBCH deficiency and provide support that HIBCH deficiency should be included in the differential for elevated hydroxy-C4-carnitine in newborn screening (NBS). METHODS: Whole exome sequencing (WES) was performed on one affected sibling. HIBCH enzymatic activity was measured in patient fibroblasts. Acylcarnitines were measured by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Disease incidence was estimated using a cohort of 61,434 individuals. RESULTS: Two siblings presented with infantile-onset, progressive neurodegenerative disease. WES identified a novel homozygous variant in HIBCH c.196C>T; p.Arg66Trp. HIBCH enzymatic activity was significantly reduced in patients' fibroblasts. Acylcarnitine analysis showed elevated hydroxy-C4-carnitine in blood spots of both affected siblings, including in their NBS cards, while plasma acylcarnitines were normal. Estimates show HIBCH deficiency incidence as high as 1 in ~130,000 individuals. CONCLUSION: We describe a novel family with HIBCH deficiency at the biochemical, enzymatic and molecular level. Disease incidence estimates indicate HIBCH deficiency may be under-diagnosed. This together with the elevated hydroxy-C4-carnitine found in the retrospective analysis of our patient's NBS cards suggests that this disorder could be screened for by NBS programs and should be added to the differential diagnosis for elevated hydroxy-C4-carnitine which is already measured in most NBS programs using MS/MS.
Keywords: Abnormalities, Multiple; Adolescent; Amino Acid Metabolism, Inborn Errors; Carnitine; Child; Child, Preschool; Cohort Studies; Exome; Female; Fibroblasts; Humans; Infant; Infant, Newborn; Leigh Disease; Male; Mass Spectrometry; Neonatal Screening; Prognosis; Retrospective Studies; Sequence Analysis, DNA; Siblings; Thiolester Hydrolases

Dosage changes of a segment at 17p13.1 lead to intellectual disability and microcephaly as a result of complex genetic interaction of multiple genes. - Carvalho, Claudia M B; Vasanth, Shivakumar; Shinawi, Marwan; Russell, Chad; Ramocki, Melissa B; Brown, Chester W; Graakjaer, Jesper; Skytte, Anne-Bine; Vianna-Morgante, Angela M; Krepischi, Ana C V; Patel, Gayle S; Immken, LaDonna; et al. (Am J Hum Genet, 2014)
The 17p13.1 microdeletion syndrome is a recently described genomic disorder with a core clinical phenotype of intellectual disability, poor to absent speech, dysmorphic features, and a constellation of more variable clinical features, most prominently microcephaly. We identified five subjects with copy-number variants (CNVs) on 17p13.1 for whom we performed detailed clinical and molecular studies. Breakpoint mapping and retrospective analysis of published cases refined the smallest region of overlap (SRO) for microcephaly to a genomic interval containing nine genes. Dissection of this phenotype in zebrafish embryos revealed a complex genetic architecture: dosage perturbation of four genes (ASGR1, ACADVL, DVL2, and GABARAP) impeded neurodevelopment and decreased dosage of the same loci caused a reduced mitotic index in vitro. Moreover, epistatic analyses in vivo showed that dosage perturbations of discrete gene pairings induce microcephaly. Taken together, these studies support a model in which concomitant dosage perturbation of multiple genes within the CNV drive the microcephaly and possibly other neurodevelopmental phenotypes associated with rearrangements in the 17p13.1 SRO.
Keywords: Abnormalities, Multiple; Acyl-CoA Dehydrogenase, Long-Chain; Adaptor Proteins, Signal Transducing; Animals; Asialoglycoprotein Receptor; Base Sequence; Cell Line; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human, Pair 17; Dishevelled Proteins; Flow Cytometry; Gene Dosage; Humans; Immunohistochemistry; Intellectual Disability; Microcephaly; Microtubule-Associated Proteins; Molecular Sequence Data; Phosphoproteins; Retrospective Studies; Sequence Analysis, DNA; Smith-Magenis Syndrome; Syndrome; Zebrafish